The Surgical and Definitive Obturator after Hemimaxillectomy of the Palate Tumor - Rifai, Yusalvi; Rhamdani, Riezki; Mude, Acing Habibie (Indonesia Prosthodontic Association, 2021)
Patient chief complaint: A 53-year-old female patient came to the UNHAS RSGM upon a referral from an ENT specialist, patient was planned to undergo surgical removal of the left upper jaw due to the presence of a tumor, the patient needed a prosthesis. Patient status: Clinical examination, there was enlargement with hard palpation of the left hard palate with involvement of teeth 21 to 27, caries in 18, 12, 38, 37 and root remnants in 17, 16, 26, 27, and 36. Patient will undergo hemimaxillectomy surgery in the area. On the panoramic radiograph, a radiopaque mass extends over the right hard palate. Treatment plan: The patient was planned to undergo surgical removal of the left upper jaw due to the presence of a tumor, needed a prosthesis (surgical obturator) after removal of the tumor for her oral cavity. Details of therapy: Then an initial impression was also performed using irreversible hydrocolloid material to obtain a diagnostic model for the maxilla and mandible. Multidisciplinary discussion was conducted with the ENT specialist. The surgical obturator was made of heat cured acrylic material, equipped with artificial teeth elements and clasps. All the abutment teeth were gripped with the half Jackson type. The clasps were placed on 18, 15, 11, and 28. the position of the obturator base in contact with the tissue. Clinical significance: The use of an obturator can help patients in swallowing, masticating, and speaking, as well as helping to restore aesthetic function.